Simulation of the parameters of the meteor radar system in order to optimize its operation - Антипов, Иван Евгеньевич; Бондарь, Евгения Юрьевна; Шкарлет, Александр Иванович (Technology audit and production reserves, 2013)
Since 1966 the Meteor Automated Radar System (MARS) has been operating at the Balakleya scientific testing ground of the Kharkov National University of Radio Electronics, which had provided with the unique scientific data on meteors and the earth's atmosphere. For a long time of operation the equipment has undergone considerable moral and physical obsolescence. The need to continue the meteoric research on the one hand, and the inability to do so on the available equipment on the other hand, requires the modernization of the complex with regard of the new objectives and new opportunities. Simple switch to the new element base without taking into account the changing of the working conditions and new research objectives is not reasonable. It is necessary to revise a number of parameters of the available equipment. A large number of factors can be found by means of modeling of the improved complex. However, the simulation can not be carried out without a major component - the model of the meteor-trail reflections. Therefore, the primary problem is to develop a model that would include the ground-based research equipment parameters and the model of the processes occurring in the meteor zone as well. The article proposes the structure of this model, presents the analytical concepts for some modeling stages and their graphic interpretation. The above model is implemented as a computer program. The above model is implemented as a computer program. It differs by the change of the signal amplitude in the meteor trail formation process; the ability to model meteor propagation to the "ultra-short" routs - between the main and offset points; as well as to determine the trail coordinates, which is necessary for further determination of the meteor radiant.